Liniowa Teoria Mikropolarnej Sprężystości - Nowacki, W. (Engineering Transactions, 1973)
The paper consists of two parts, the first part dealing with helastokinetics, the second one – with elastostatics. In both parts an important role is played by elastic potentials and stress functions of the Galerkin type. Extensive discussion concerns the most simple, two-dimensional problems of plane strain and axisymmetric stress. In the section dealing with elastostatics, the role of the theorem by H. Schaefer in superposing the solutions is demonstrated.